Increasing participation in incentive programs for biodiversity conservation. Issue 5 (1st July 2013) - Sorice, Michael G.; Oh, Chi-Ok; Gartner, Todd; Snieckus, Mary; Johnson, Rhett; Donlan, C. Josh
Abstract : Engaging private landowners in conservation activities for imperiled species is critical to maintaining and enhancing biodiversity. Market‐based approaches can incentivize conservation behaviors on private lands by shifting the benefit–cost ratio of engaging in activities that result in net conservation benefits for target species. In the United States and elsewhere, voluntary conservation agreements with financial incentives are becoming an increasingly common strategy. While the influence of program design and delivery of voluntary conservation programs is often overlooked, these aspects are critical to achieving the necessary participation to attain landscape‐scale outcomes. Using a sample of family‐forest landowners in the southeast United States, we show how preferences for participation in a conservation program to protect an at‐risk species, the gopher tortoise ( Gopherus polyphemus ), are related to program structure, delivery, and perceived efficacy. Landowners were most sensitive to programs that are highly controlling, require permanent conservation easements, and put landowners at risk for future regulation. Programs designed with greater levels of compensation and that support landowners' autonomy to make land management decisions can increase participation and increase landowner acceptance of program components that are generally unfavorable, like long‐term contracts and permanent easements. There is an inherent trade‐off between maximizing participation and maximizing the conservation benefits when designing a conservation incentive program. For conservation programs targeting private lands to achieve landscape‐level benefits, they must attract a critical level of participation that creates a connected mosaic of conservation benefits. Yet, programs with attributes that strive to maximize conservation benefits within a single agreement (and reduce risks of failure) are likely to have lower participation, and thus lower landscape benefits. Achieving levels of landowner participation in conservation agreement programs that deliver lasting, landscape‐level benefits requires careful attention not only to how the program structure influences potential conservation benefits, but also how it influences landowners and their potential to participate.